A fluorescence strategy for direct quantification of arm components in mikto-arm star copolymers. Issue 14 (23rd March 2022) - Shi, Wencheng; Wu, Boyu; Guo, Xiaofeng; Feng, Anchao; Thang, San H.
Abstract : The arm components of mikto-arm star polymers were quantitatively analyzed with a novel fluorescence strategy. Abstract : Fluorescent end-functional mikto-arm star copolymers were prepared by an "arm-first" approach mediated by a mixture of macro-RAFT agents. RAFT copolymerization of coumarin-POEGMA, boron-dipyrromethene (BODIPY)-PDMA and bisindolylmaleimide (BIM)-PNIPAM with different fluorophore-labeled end-groups was performed with polyethylene glycol diacrylate as a cross-linker. The fluorescence spectra of fluorophore-labeled homopolymers showed that there was a good linear correlation existing between fluorescence intensity and polymer concentration in dilute solutions. According to the fluorescence results, after carefully choosing the peaks and calculation, the arm components of star polymers can be quantitatively analyzed with obvious similarity to 1 H NMR approaches which are considered to be less valid in a complicated chemical environment. Overall, it is reasonably expected that the current study expands the characterization methods for star polymers and promotes the development of the synthesis of well-defined multifunctional star polymers.